Economic optimum nitrogen rate analysis for feed and malting barley - Reussi Calvo, Nahuel Ignacio; Carciochi, Walter; Prystupa, Pablo; Queirolo, Ignacio; Sainz Rozas, Hernan Rene (Wiley, 2022)
The malt industry has specific requirements for malting barley (Hordeum vulgare L.) grain protein concentration (from 9.5 to 13%) and size (>85%), which could be affected by nitrogen (N) fertilization. We aimed to (a) define and explain the economic optimum nitrogen rate (EONR) for grain yield in feed (EONRf) and malting barley (EONRm), and (b) analyze if grain quality requirements are reached at the EONRm. We evaluated six N rates (0, 40, 80, 120, 160, and 200 kg N ha−1) in field experiments (14 site-years). At each site-year, the EONR was calculated using two fertilizer cost to grain price ratios, 6:1 for feed and 4:1 for malting barley. On average, maximum yield and protein response to N were 1,681 kg ha−1 and 2%, respectively. There was no consistent effect of N fertilization on grain size. The EONRf was explained by N availability and maximum yield response to N (y = 130 – 0.37N availability + 0.03N response, r2 = .89), and EONRm was explained solely by N availability (y = 320 – 0.93N availability, r2 = .75). The overall EONRm was 134 kg N ha−1. At sites with low soil N availability and high yield response to N, an average N rate of 69 kg ha−1 greater than the EONRm was necessary to reach 9.5% protein. Otherwise, the EONRf could be used (106 kg N ha−1) and grains be sold as feed barley. These results are useful to adjust N fertilizer recommendations to satisfy the malting industry demand while reducing the economic and environmental impacts of fertilization.